Board game-based education on helminthiasis knowledge of elementary school students: An effectiveness study - Rusjdi, Selfi Renita; Hendra, Gabriel Septian; Fadhilah, Maisarah; Muhammad Nur Alif Johar; Utami, Mutia; Rahmaddiansyah, Refa; Wulandari, Wulandari; Yustian, Ahmad Raffi; Aisyah, Siti; Kaltsum, Nilam Fa'izah; Satiya, Selin Faysa (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Background: School-aged children are particularly vulnerable to soil-transmitted helminths (STH) infections due to frequent exposure to contaminated soil during play and poor personal hygiene practices. Although games have been widely used as educational tools in health promotion, there is limited research on the effectiveness of board games specifically designed to prevent STH infections in children.Objective: This study aimed to evaluate the effectiveness of a board game-based educational intervention in enhancing knowledge of STH among elementary school students.Methods: Analytical experimental design using a pre-test and post-test intervention approach without a control group was employed. The subjects of this study were elementary school students in grades 3 to 6 who met specific criteria. A total of 94 students participated. Knowledge was assessed using questionnaires. The intervention involved small-group sessions (4–6 students per group) using a custom-designed educational board game about STH. The collected data were analyzed using a dependent t-test, while multivariate ordinal regression was employed for multivariate analysis. Results: The average test score improved from 0.60 (± 0.15) to 0.74 (± 0.14) post-intervention, representing a significant 14% increase in knowledge (p = 0.00). Age was not a significant predictor of post-test performance (β = 0.310; p = 0.429). Male students (β = 1.068; p = 0.013) and those in grade 4 (β = 2.031; p = 0.036; OR = 7.62, 95% CI: 1.15–50.56) were significantly more likely to achieve higher post-test scores.Conclusion: Board game-based education effectively improved knowledge about soil-transmitted helminth infection among elementary school students. This study offers novel evidence supporting the use of board games for helminthiasis prevention.